Seagrass Posidonia oceanica diel pH fluctuations reduce the mortality of epiphytic forams under experimental ocean acidification. (September 2019) - Ramajo, Laura; Lagos, Nelson A.; Duarte, Carlos M.
Abstract: It is hypothesized that pH fluctuations produced by seagrasses metabolism may confer marine calcifiers resistance to ocean acidification. Here, we tested this thesis by comparing the net population growth rate (NPGR) of a foraminifer species ( Rosalina sp.) epiphytic of Mediterranean seagrass ( Posidonia oceanica ) to average current and projected pH scenarios under either stable conditions or diel fluctuations in pH of 0.3 units; variations similar to that experienced in their habitat. No significant differences were found in NPGRs between the fluctuating and stable pH treatments at current pH levels. NPGRs in treatments where pH fluctuated did not present significant differences to the treatment with high and stable pH conditions. In contrast, foraminifers exposed to stable low pH regimes experienced a steep decline in NPGR. These results suggest that diel pH fluctuations generated by P. oceanica photosynthetic activity could confer resistance to ocean acidification to Rosalina sp. Highlights: Forams epiphyte of Posidonia oceanica are resistant to ocean acidification scenarios. Seagrasses may provide "refugia" from ocean acidification to associated biota. There is an urgent need to incorporate pH fluctuations in the experimental designs.